A Bibliometric Analysis of Crowd-Funding and Entrepreneurship Research - Arora, Ashish; Sagar (Information Research Communications, 2026)
Aim This study provides a comprehensive overview of global scholarship on crowdfunding and entrepreneurship by synthesizing influential authors, documents, journals, countries, and institutions. It examines intellectual collaboration, citation networks, key thematic clusters, and emerging research fronts. Materials and Methods Using data from 1986 to 2025 collected from Scopus and Web of Science, the study employed bibliometric tools like VOSviewer and Biblioshiny. A dataset of 3,817 publications was compiled through broad keyword searches and data cleaning. This enabled detailed descriptive analyses, science mapping, and thematic exploration of historical and current trends. Results Crowdfunding research surged after 2013, peaking between 2020 and 2024. Influential authors include Vismara and Schwienbacher, with journals such as Journal of Business Venturing and Small Business Economics leading the discourse. The United States dominates in publications and citations. Collaboration networks show moderate connectivity across authors, countries, and institutions. Core themes focus on entrepreneurial finance, human and social capital, and sustainability, while emerging areas include platform governance, investor behavior, and digital innovation. Conclusion This bibliometric analysis integrates a fragmented field, highlighting key trends and collaborations. It offers insights for scholars, practitioners, and policymakers to foster inclusive, sustainable crowdfunding ecosystems. The study emphasizes enhancing transparency, promoting global collaboration, responsibly adopting new technologies, and addressing ethical and diversity challenges to support the field’s growth.
Keywords: Bibliometric Analysis; Entrepreneurship Crowdfunding; New-venture financing; Scopus database; Startup funding; Vos viewer.